Broad CD8(+) T cell cross-recognition of distinct influenza A strains in humans - Grant, Emma J. (Nat Commun, 2018)
Newly-emerged and vaccine-mismatched influenza A viruses (IAVs) result in a rapid global spread of the virus due to minimal antibody-mediated immunity. In that case, established CD8(+) T-cells can reduce disease severity. However, as mutations occur sporadically within immunogenic IAV-derived T-cell peptides, understanding of T-cell receptor (TCRαβ) cross-reactivity towards IAV variants is needed for a vaccine design. Here, we investigate TCRαβ cross-strain recognition across IAV variants within two immunodominant human IAV-specific CD8(+) T-cell epitopes, HLA-B*37:01-restricted NP(338-346) (B37-NP(338)) and HLA-A*01:01-restricted NP(44-52) (A1-NP(44)). We find high abundance of cross-reactive TCRαβ clonotypes recognizing distinct IAV variants. Structures of the wild-type and variant peptides revealed preserved conformation of the bound peptides. Structures of a cross-reactive TCR-HLA-B37-NP(338) complex suggest that the conserved conformation of the variants underpins TCR cross-reactivity. Overall, cross-reactive CD8(+) T-cell responses, underpinned by conserved epitope structure, facilitates recognition of distinct IAV variants, thus CD8(+) T-cell-targeted vaccines could provide protection across different IAV strains.